Welfare and Fiscal Implications from Increased Gasoline Prices in the Islamic Republic of Iran - Atamanov, Aziz; Mostafavi Dehzooei, Mohammadhadi; Wai-Poi, Matthew (World Bank, Washington, DC, 2020)
Facing a fiscal crisis, the Islamic Republic of Iran decided to increase gasoline prices at the end of 2019. This paper estimates the impact of the price increase on household welfare and government revenue, using the most recent Household Expenditure and Income Survey conducted by the Statistical Center of Iran in March 2018-March 2019. The paper looks at the direct and indirect impacts of the reform and quantifies the compensatory cash transfer program the government instituted. Despite very regressive gasoline subsidies benefitting the rich the most, the increase in gasoline prices is found to affect the poor to a greater extent due to larger negative indirect impacts as well as their relatively low incomes. In total, poverty is estimated to increase by about 2.9 percentage points, with the direct impact accounting for a third of this increase. The proposed government scheme, if targeted perfectly to the poorest 18 million households, would fully compensate the poorest bottom 50 percent of the population and reduce poverty to below pre-reform levels. The annual cost of the program will be around 338 trillion rials, which accounts for 77 percent of the estimated total savings from the subsidies reform (439 trillion rials).